Strategi Perencanaan Promosi Efektif Untuk Meningkatkan Kunjungan Di NUART Sculpture Park - Pramuditha, Andini Putri Pramuditha; Setiawati, Linda Setiawati; Khoerunnisa, Lutfi Khoerunnisa (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
NuArt Sculpture Park is one of the art galleries that has the potential to grow rapidly through the right promotion strategy. NuArt Sculpture Park is a 3 hectare art gallery or sculpture park located in Bandung, West Java and managed privately by I Nyoman Nuarta, a sculptor who was born in Bali on November 14, 1951. This gallery exhibits various sculptural works of art by artist Nyoman Nuarta. With various types of works on display, Nuart Sculpture Park is able to develop rapidly by carrying out effective promotions to attract public attention. The purpose of this study is to find out the promotions carried out by NuArt Sculpture Park and effective promotions for the future. By using a descriptive qualitative research method with a search for data focusing on observation and review of the literature this research provides an overview of the promotion strategy. The results of the study prove that NuArt Sculpture Park tends to promote on social media using only an Instagram account, even though this gallery has other social media accounts on Twitter and YouTube. In terms of promotion, it can be concluded that NuArt Sculpture Park still does not manage the online market properly and does not manage its accounts simultaneously and consistently. To overcome this, NuArt Sculpture Park needs to understand and manage social media accounts and package promotional information into unique and creative content.